2021
DOI: 10.1111/1744-9987.13708
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing arteriovenous fistulas: A multicenter study

Abstract: In this cross-sectional, descriptive study, the arteriovenous fistulas (AVF) of HD patients were evaluated by physical examination and factors associated with AVF function and longevity were investigated. Data were collected using a patient information form and the Arteriovenous Fistula Assessment Scale (AVF-AS). The study population included 279 patients under chronic HD treatment. Their mean age was 61.14 ± 14.00 years and 58.6% were men. Age, AVF location, and number of AVFs created were identified as facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Bulbul et al, [6] reported that the risk of complications was greater with AVFs at the upper arm and elbow level than in those at the wrist and snuffbox level. The cephalic venous arch receives the blood flow of the upper arm cephalic vein to be drained into the subclavian vein at a right angle.…”
Section: Discussionmentioning
confidence: 99%
“…Bulbul et al, [6] reported that the risk of complications was greater with AVFs at the upper arm and elbow level than in those at the wrist and snuffbox level. The cephalic venous arch receives the blood flow of the upper arm cephalic vein to be drained into the subclavian vein at a right angle.…”
Section: Discussionmentioning
confidence: 99%
“…Birçok ülkede olduğu gibi ülkemizde de arteriyovenöz fistül ile ilişkili problemlerin geçmişte ve gelecekte de önemli bir sorun olması ve bu problemlerin morbidite oranını artırmasından dolayı bu konunun ülkemizde ağırlıklı olarak çalışıldığı düşünülmektedir. 32 Ayrıca literatürde birçok araştırmada, hemodiyaliz tedavisi uygulanan bireylerde arteriyovenöz fistüle yönelik öz bakım davranışlarının düşük ve orta düzeyde olduğu belirtilmiştir ve bu durumun da ülkemizde bu konunun ağırlıklı olarak çalışılmasında etkili olabileceği düşünülmektedir. [33][34][35] Dergi analizi ve atıf alan dergiler ağ analizi, Nephrology Nursing Journal, Journal of Renal Care ve Renal Society of Australasia Journal dergilerinin hemşirelikte en fazla hemodiyaliz araştırmalarını yayımlayan dergiler olduğunu ve American Journal of Kidney Diseases'in en çok atıf alan dergi olduğunu göstermiştir.…”
Section: Anahtar Keli̇meleri̇n Anali̇zleri̇unclassified
“…Maintaining AVF patency is vital for hemodialysis (HD) treatment; however, an AVF cannot be used permanently, and AVF failure is a common reason for hospitalization and morbidity of MHD patients. Researchers have shown that the mean service life of an AVF is 4.15 years, and the pooled primary patency rate is only 60% 4,5 . AVF can fail after surgery, which is primarily caused by AVF maturation failure and AVF stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that the mean service life of an AVF is 4.15 years, and the pooled primary patency rate is only 60%. 4,5 AVF can fail after surgery, which is primarily caused by AVF maturation failure and AVF stenosis. Venous neointimal hyperplasia (VNH) and vascular endothelial injury are the main causes of AVF stenosis.…”
Section: Introductionmentioning
confidence: 99%